2015
DOI: 10.1007/s00039-015-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Hitchin representations along internal sequences

Abstract: Using the work of Bonahon-Dreyer and Fock-Goncharov, one can construct a real-analytic parameterization for the PSL(n,R) Hitchin component of a surface S, that is explicitly analogous to the Fenchel-Nielsen coordinates on the Teichmuller space of S. Given a Hitchin representation, we give a lower bound on the "length" of any closed curve on S in terms of the parameters describing this representation. We then show that this lower bound is good enough to produce large families of sequences in the Hitchin compone… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
(106 reference statements)
0
36
0
Order By: Relevance
“…However, it is clear that the intersection number is not symmetric on the Hitchin component. For example, one may use the work of Zhang [94,95] to exhibit for all K > 1 and…”
Section: Corollary 510 Entropy Varies Analytically Over H D (S) Andmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is clear that the intersection number is not symmetric on the Hitchin component. For example, one may use the work of Zhang [94,95] to exhibit for all K > 1 and…”
Section: Corollary 510 Entropy Varies Analytically Over H D (S) Andmentioning
confidence: 99%
“…(2) Tengren Zhang [94,95] showed that, for all d, there exist large families of sequences of Hitchin representations with entropy converging to 0. Nie [64] had earlier constructed specific examples when d = 3.…”
Section: Rigidity Theorems For Hitchin Representationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance compactifications of spaces of representations of Γ have been introduced and studied in [Par12,Ale08,Le12]. In the context of Hitchin representations, asymptotic properties of diverging sequences are studied in [Zha13,Zha14,CL14,Lof15,Par15,KNPS15,MSWW14].…”
Section: Introductionmentioning
confidence: 99%